2003
DOI: 10.1046/j.1365-3059.2003.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation among asexual progeny of Phytophthora infestans detected with RAPD and AFLP markers

Abstract: Genotypic variation among 32 single-zoospore isolates (SZI) of Phytophthora infestans , derived asexually from two hyphal-tip parental isolates (PI-105 and PI-1) of the US-8 genotype, was assessed with 80 random amplified polymorphic DNA (RAPD) primers and 18 amplified fragment length polymorphic DNA (AFLP) primer pairs. In previous investigations, the SZIs from parental isolate PI-105 showed high levels of virulence variability and were differentiated into 14 races, whereas the SZIs from PI-1 showed identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 30 publications
(29 reference statements)
1
24
0
3
Order By: Relevance
“…Evidence of mitotic recombination in Phytophthora species has been previously reported (Sansome 1980, Goodwin, Cohen & Fry 1994, Abu-El Samen, Secor & Gudmestad 2003, Dobrowolski et al 2003 and could explain the slight variations observed in our AFLP profiles within each population. P. ramorum is known to rapidly reproduce asexually through the formation of large numbers of sporangia, which either germinate directly or differentiate into motile zoospores.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Evidence of mitotic recombination in Phytophthora species has been previously reported (Sansome 1980, Goodwin, Cohen & Fry 1994, Abu-El Samen, Secor & Gudmestad 2003, Dobrowolski et al 2003 and could explain the slight variations observed in our AFLP profiles within each population. P. ramorum is known to rapidly reproduce asexually through the formation of large numbers of sporangia, which either germinate directly or differentiate into motile zoospores.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, a recent study detected differences in sporangial morphology between isolates from the USA and Europe (D. Hu¨berli & M.G., unpubl.). The lack of correlation among phenotypic and genotypic variation has been demonstrated in other Phytophthora species (Dudzinski, Old & Gibbs 1993, Abu-El Samen, Secor & Gudmestad 2003. Phenotypic variation within a molecular clone was also reported for P. cinnamomi in Western Australia (Hu¨berli et al 2001).…”
Section: Discussionmentioning
confidence: 87%
“…From 53 progenies, 52 isolates had lower pathogenicities compared to their parents. Abu-El Samen et al (2003) found a genotypic variability among the asexual progenies of P. infestans.…”
Section: Discussionmentioning
confidence: 93%
“…Berbagai metode analisis telah digunakan untuk mempelajari keragaman populasi Phytophthora spp., di antaranya adalah Restriction Fagment Length Polymorphisms (RFLP) (Goodwin et al, 1992), analisis sekuen (Schena et al, 2006), single nucleotide polymorphisms (SNPs) (Kroon et al, 2004;Bilodeau et al, 2007), Random Amplified Polymorphic DNA (RAPD) (Cooke et al, 1996;Abu-El Samen et al, 2003), Amplified Fragment Length Polymorphism (AFLP) (Ivors et al, 2004;Bowers et al, 2007), microsatellites (Dobrowolski et al, 2003;Lees et al, 2006), dan mitochondrial haplotypes (Gavino & Fry, 2002;Martin, 2008). Analisis keragaman genetik P. palmivora memerlukan penanda genetik yang handal dan informatif.…”
Section: Pendahuluanunclassified